Algal Biomass Utilization toward Circular Economy - Magdalena Zabochnicka; Małgorzata Krzywonos; Zdzisława Romanowska-Duda; Szymon Szufa; Ahmad Darkalt; Muhammad Mubashar (Life, 2022)
A review of the potential areas of algal biomass utilization has already been conducted. In addition to lowering the greenhouse effect and contributing to the decrease in the amounts of harmful substances in the air and water, attention has been paid to the possibility of utilizing algal biomass as a feedstock for the production of environmentally friendly products. The circular economy addresses the benefits to the environment, economy and society. The utilization of algal biomass benefits the environment by reducing greenhouse gases emissions as well as water and wastewater treatment, benefits the economy by producing biofuels, and benefits society by producing food, cosmetics, pharmaceuticals, fertilizers and feed for animals.